Evaluation of Mechanical Properties and Durability of Concrete Pavement Containing Electric Arc Furnace Slag and Carbon Nanostructures - Abolfazl Mohammadi Janaki; Gholamali Shafabakhsh; Abolfazl Hassani (Journal of Rehabilitation in Civil Engineering)
The destructive effects of global warming have attracted attention to the optimal using of resources and recycling. Therefore, slag has been considered as a solution in various industrial sectors including the road construction. Also, among the new materials, cement carbon nanostructures which can improve the concrete mechanical properties and resistance are used. These nanostructures are produced through Chemical Vapor Deposition method during the cement production process on the type II cement. In this study, it is aimed to improve the mechanical properties and resistance of concrete pavements with slag and cement carbon nanostructures. The results showed that using 66% slag and 5% cement carbon nanostructures (SC66N5) have been shown the best performance in concrete pavements. Increasing the amount of slag and carbon nanostructures enhance the compressive strength, flexural strength, tensile strength, chlorine passing current and durability against freezing and thawing cycles, and decrease permeability and water absorption percentage. The results showed that in SC66N5 28-day sample, the compressive strength (52%), flexural strength (32%), tensile strength (53%), chlorine passing current (88%) and passing ultrasonic pulse velocity after freezing and thawing (7%) are increased with respect to the cement concrete sample. Furthermore, the permeability (46%), water absorption percentage (45%), weight loss after freezing and thawing cycles (78%) are reduced in comparison to the cement concrete sample. The results revealed that using slag and cement carbon nanostructures improve the durability of concrete pavements.